The Atlantic in world history - Kupperman, Karen Ordahl (Oxford University Press, 2012)
Includes bibliographical references (p. [127]-131) and index.; Introduction: thinking Atlantically -- Atlantic memories -- Atlantic beginnings -- Atlantic people -- Commodities: foods, drugs, and dyes -- Eighteenth-century realities -- Epilogue: the Atlantic.